INTEGRATING DIGITAL INFORMATION TECHNOLOGIES INTO THE METHODOLOGICAL FRAMEWORK FOR TRAINING SPECIALIZED TRANSLATORS IN A MULTIDISCIPLINARY EDUCATIONAL CONTEXT - Bakirova Khilolakhon Botiraliyevna (ARAB TILI GLOBALLASHUV DAVRIDA: INNOVATSION YONDASHUVLAR VA O‘QITISH METODIKASI MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2025)
The rapid development of digital information technologies has significantly influenced the field of translation studies and reshaped the professional training of specialized translators. This study examines how digital tools can be systematically integrated into the methodological framework for training translators operating in multidisciplinary environments. The research explores the effectiveness of technology-enhanced instruction in improving domain-specific translation competence, cognitive flexibility, and professional readiness. Using a mixed-methods approach that combines theoretical analysis, survey data, and experimental observation, the study reveals that the structured integration of digital platforms, terminology management systems, and corpus-based resources substantially increases translation accuracy and efficiency. The findings contribute to the advancement of translator education by proposing a technology-driven methodological model suited to contemporary academic contexts.